Generation and characterization of the LINC01405 knockout human embryonic stem cell line - Yaping Xu; Hongchun Wu; Jingxiu Jiang; Lingqun Ye; Kaili Hao; Kunjun Han; Shijun Hu; Wei Lei; Zhikun Guo (Stem Cell Research)
Long Intergenic Non-Protein Coding RNA 1405 (LINC01405), with known elevated expression in muscle, has been linked to a number of musculo-skeletal conditions. By utilizing the CRISPR/Cas9 gene editing system, we generated a LINC01405 knockout human embryonic stem cell (hESC) line. This line remains human stem cell-like morphology and pluripotency, exhibits a normal karyotype, and can differentiate into cells from all three germ layers. This cell line will be an invaluable model for the research on LINC01405's role in normal development of cardiac and skeletal muscle, and their diseases.